PERAN GURU SANDARAN PEMBIMBING ASRAMA DALAM MEMBENTUK KARAKTER DISIPLIN SISWA KELAS V MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Laely, Dinda Rahmatul Nur; Dadan Mardani; Dewi Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the role of Dormitory Mentor Teachers in shaping the disciplinary character of fifth-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun. The research employed a qualitative descriptive approach. The subjects consisted of dormitory mentor teachers and fifth-grade students selected purposively. Data were collected through observation, interviews, and documentation. The results showed that dormitory mentor teachers act as role models, guides, directors, and controllers in instilling student discipline through habituation, exemplary behavior, and continuous supervision. Supporting factors include students’ awareness, an orderly dormitory environment, and teacher collaboration, while inhibiting factors are differences in student characteristics and lack of supervision outside dormitory hours. Thus, dormitory mentor teachers play an essential role in shaping students’ disciplinary character through consistent modeling and guidance.